1997
DOI: 10.1038/nsb1297-1003
|View full text |Cite
|
Sign up to set email alerts
|

The structure of mammalian 15-lipoxygenase reveals similarity to the lipases and the determinants of substrate specificity

Abstract: Here we report the first structure of a mammalian 15-lipoxygenase. The protein is composed of two domains; a catalytic domain and a previously unrecognized beta-barrel domain. The N-terminal beta-barrel domain has topological and sequence identify to a domain in the mammalian lipases, suggesting that these domains may have similar functions in vivo. Within the C-terminal domain, the lipoxygenase substrate binding site is a hydrophobic pocket defined by a bound inhibitor. Arachidonic acid can be docked into thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
470
1
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 425 publications
(491 citation statements)
references
References 37 publications
16
470
1
4
Order By: Relevance
“…However, CD/MCD spectroscopic data are more sensitive indicators of the first coordination sphere, as seen by the variation of the ligand arrangement depending on experimental conditions (28). While ligand bond lengths derived from crystallography may have to be viewed with caution, general structural features are represented reliably in the crystal structures; specifically, the hydrogen bond network connecting the first and second coordination spheres is welldefined in all known mammalian and plant LOs (24)(25)(26)(27). In this study, the correlation of Fe II ligand field spectroscopic data with structural information has allowed us to investigate the roles individual interactions within the H-bond network play in the modulation of enzyme reactivity in LOs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, CD/MCD spectroscopic data are more sensitive indicators of the first coordination sphere, as seen by the variation of the ligand arrangement depending on experimental conditions (28). While ligand bond lengths derived from crystallography may have to be viewed with caution, general structural features are represented reliably in the crystal structures; specifically, the hydrogen bond network connecting the first and second coordination spheres is welldefined in all known mammalian and plant LOs (24)(25)(26)(27). In this study, the correlation of Fe II ligand field spectroscopic data with structural information has allowed us to investigate the roles individual interactions within the H-bond network play in the modulation of enzyme reactivity in LOs.…”
Section: Discussionmentioning
confidence: 99%
“…An examination of the crystal structure of wildtype (wt) sLO-1 (14) indicates the presence of an extensive hydrogen bonding network that connects the weakly bound asparagine ligand (Asn694) via the two second coordination sphere residues, Gln697 and Gln495, to an equatorial iron ligand, His499 (Figure 1). A similar network is also present in 15-rLO (27), and it was speculated that interactions between the substrate and this hydrogen bond network are responsible for the observed sensitivity of the coordination number in ferrous sLOs (14). Previously, Gln697 and Gln495 were mutated (Q697E, Q697N, Q495E, and Q495A) ( Figure 1), and their kinetic properties were related to their crystal structures (14).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, the smaller rabbit 15-LOX-1 (molecular mass 75 kDa) comprises a C-terminal domain of about 550 amino acid residues, largely helical, and a small N-terminal domain of 111 amino acid residues, consisting of two, four-stranded antiparallel b-sheets. 16 The three-dimensional crystal structures of LOX-1 and 15-LOX-1, both 15-lipoxygenases, 1 are largely overlapping, as shown in Scheme 1. On the basis of the spatial distribution pattern of the B-values of the soybean LOX-1 crystal structure, it was suggested that the N-terminal domain may rock across the surface of the catalytic domain, a motion apparently compatible with the short random coil segment (amino acid residues 145-160) connecting the two domains.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 and that of a rabbit 15-LOX-1-inhibitor complex 16 have been reported so far. In addition, three-dimensional models of the human 5-LOX have been deduced on the basis of the rabbit 15-LOX-1 crystal structure and multiple amino acid alignments.…”
Section: Introductionmentioning
confidence: 99%